KUALITAS FISIK SILASE AMPAS KECAP DENGAN ADITIF TANIN AKASIA (Acacia mangium Wild.) DAN ADITIF LAINNYA - Sadarman Sadarman; M Ridla; Nahrowi Nahrowi; R Ridwan; R P Harahap; R A Nurfitriani; A Jayanegara (Jurnal Peternakan, 2019)
Tannin is one of plant secondary metabolites that could protect proteins from various microbes, both in feed material and in rumen. Tannin can be used as an additive in the silage production process, especially high-protein feed material. The study aimed to evaluate the physical quality of soy sauce by-product silage treated with Acacia mangium Wild. tannin (AT; condensed tannin). This study used the fresh soy sauce by-product, tannin of acacia and chestnut (CT; hydrolysable tannin), BAL and propionate acid (PA). Soy sauce by-product was fermented in silo with a capacity of 1.3 Kg. This experiment was arranged in a complete randomized design with 6 treatments and 3 replications. The treatments were (R1) fermented soy sauce by-product, (R2) R1 + BAL, (R3) R1 + 2% AT, (R4) R1 + 2% CT, (R5) R1 + 0.5% PA and (R6) R1 + combination of 1% AT, 1% CT and 0.5% PA. The observed variables were the loss of dry matter (%), temperature (⁰C), smell, color and emerged fungus on silage. Analysis of variance was performed by SPSS version 23. For any significant difference between treatments was evaluated by DMRT at level of confident 5%. The result showed that AT suppressed the loss of dry matter up to 0.91%, and produced no smell with black color such as soybean color. The silage temperature was relatively similar for about 28.9-29.4 ⁰C, no emerged fungus, and did not able to maintain the normal silage temperature. Nevertheless, the use of acacia tannin could produce a good quality soy sauce by-product silage.